Multicentric retrospective analysis of platinum‐pemetrexed regimens as first‐line therapy in non‐squamous non‐small cell lung cancer patients: A "snapshot" from clinical practice. Issue 2 (7th December 2017) - Cortellini, Alessio; Gambale, Elisabetta; Cannita, Katia; Brocco, Davide; Parisi, Alessandro; Napoleoni, Luca; Masedu, Francesco; Irtelli, Luciana; De Tursi, Michele; Natoli, Clara; Ficorella, Corrado
Abstract : Background: The major challenge for treating non‐squamous (non‐Sq) non‐small cell lung cancer (NSCLC) patients without actionable biomarkers is the actual selection of proper treatment, weighing expected clinical outcomes and safety profile. Methods: Consecutive non‐Sq NSCLC patients were treated with platinum‐pemetrexed (PP) doublets in clinical practice. Subgroup analyses were conducted in patients treated with standard (s)PP and modified (m)PP doublets (because of age, performance status, and/or comorbidities) and in patients treated with cisplatin‐based and carboplatin‐based PP doublets. Activity, efficacy, safety, and toxicities were evaluated. Results: From November 2009 to April 2017, 111 patients were treated: 87 (78.4%) with sPP and 24 (21.6%) with mPP; 76 (68.5%) with cisplatin‐based and 35 (31.5%) with carboplatin‐based regimens. The objective response rate (ORR), median progression‐free survival (PFS), and median overall survival (OS) were 49.0%, 7, and 13 months in the entire patient population, respectively. We found no significant differences in ORR, median PFS, and median OS between sPP and mPP. Cisplatin‐based PP showed higher ORR (53.7%) versus carboplatin‐based PP (38.7%) and longer PFS (7 vs. 6 months; P  = 0.028) and OS (18 vs. 11 months; P  = 0.006). We confirm that carboplatin has a better toxicity profile than cisplatin. The received dose‐intensities were ~80% of standard full doses. Conclusions: Accurate management allowed us to treat the majority of advanced non‐Sq NSCLC patients with PP combination therapy without significant differences in ORR, median PFS, and median OS. Even considering the selection bias, our data seems to confirm the greater effectiveness of cisplatin‐based over carboplatin‐based regimens.